2016
DOI: 10.1111/jch.12881
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Homocysteine‐Related Hypertension in Patients With Chronic Kidney Disease

Abstract: Patients with both hypertension and hyperhomocysteinemia, termed H‐type hypertension, have a high risk for cardiocerebrovascular diseases. However, little is known about the prevalence of H‐type hypertension or its role in target organ damage in patients with chronic kidney disease (CKD). The authors recruited 1042 patients with CKD who were admitted to their hospital division. Multiple linear regression analyses were used to evaluate the association between H‐type hypertension and renal/cardiovascular paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Similar to homocystinuria patients, in CKD patients, aged and well-nourished population substantial evidences of hyperhomocysteinemia is established [127-129]. It is still not conclusive whether hyperhomocysteinemia causes hypertension in these patients [130, 131]. …”
Section: Involvement Of Thiol Homocysteine and H2s In Renovascularmentioning
confidence: 99%
“…Similar to homocystinuria patients, in CKD patients, aged and well-nourished population substantial evidences of hyperhomocysteinemia is established [127-129]. It is still not conclusive whether hyperhomocysteinemia causes hypertension in these patients [130, 131]. …”
Section: Involvement Of Thiol Homocysteine and H2s In Renovascularmentioning
confidence: 99%
“…Hyperhomocysteinemia might cause renal damage through these mechanisms. Conversely, renal dysfunction elevates homocysteine concentration, probably due to decreasing renal metabolic extraction [15]. Thus, there exist bidirectional, functional relationships between hyperhomocysteinemia and decreased renal function.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by our finding that homocysteine level was higher in patients with hypertension and that it did not correlate with blood pressure values measured during hospitalization. Hyperglycemia, high blood pressure, and hyperhomocysteinemia [15,26,27] all accelerate atherosclerosis. Thus, we must assume that subjects with hyperhomocysteinemia have a long history of diabetes or hypertension and very high risk for atherosclerotic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al demonstrated that the concentration of Hcy is independently associated with the occurrence of early diabetic nephropathy in Chinese patients [8]. In addition, Ye et al found that the prevalence of both hypertension and HHcy was high and associated with target organ damage in patients with CKD [9]. Moreover, Eun-Hee Cho et al carried out a nested case-control study in patients with type 2 diabetes and found that HHcy was associated with an increased risk of MAU [10].…”
Section: Introductionmentioning
confidence: 99%